A study on the skeletal and muscular disorders and assessment of the physical position during working with the RULA method in dentistry units of Ilam city health centres in 1390 - Ali mohammad KARAMPOOR; Hojatollah KAKAEI; zahra ZARGOSH; hojatollah HJIZADEH; Hakim BKRI; Ali abbas HASANI (Shahid Sadoughi University of Medical Sciences, 2020)
Introduction: Musculoskeletal disorders are multi factorial phenomena and they are developed  under the influence of several causes  . Dental jobs involve  risk factors that result in  musculoskeletal disorders, generally  they are divided in to four categories including morphological factors, genetic factors, social factors, psychological factors and biomechanical. In this study regarding  the specific bodily  position of the dentists during their work a survey  has been  carried out on the prevalence of musculoskeletal disorders in Ilam city dentists. Methods : In this descriptive analytical study the positions of dentists  working in Ilam city health centres during their work with RULA have been assessed. Skeletal and muscular disorders prevalence rate has been determined by using( Nordic) standard questionnaire Results : In this study 18 dentist have participated with the mean age of  39/2 years and with the range of  (25 - 47 ) years of age , from this number  7/16% were  ( 3 women ) and 83/3% were ( 15 men ). The  12 months prevalence of disorders  in different regions of the body were particularly located in the waist  77/8% , both neck and back 66/7 % ,  and the knees 38/9% respectively. The findings obtained from RULA showed that 16/7٪ persons were at the priority correction action level 2 and  83/3٪ persons  were at the priority correction action level 3. Conclusion : According to the achieved  results due to the pain in different body regions, the dentists  have missed many days of work and daily activities ,therefore designing sports and training programs can be helpful in the prevention of musculoskeletal disorders.